EFEKTIVITAS EFFLEURAGE MASSAGE TERHADAP PENURUNAN SKOR EPDS PADA IBU POSTPARTUM PRIMIPARA - Artathi Eka Suryandari; Dyah Fajarsari (Ensiklopedia of Journal, 2023)
Background: Psychological adaptation in postpartum women includes three phases, namely the taking in phase, the taking hold phase, and the letting go phase. Postpartum mothers who can go through these three phases usually experience the postpartum period, but due to various factors, namely, 30% - 50% of postpartum mothers worldwide experience postpartum depression. Objectives: The purpose of this study is to evaluate whether or not effleurage massage is useful in lowering EPDS scores in first-time postpartum mothers. Methods: The Groups Pretest-Posttest Design was utilized for the research in this study, which was of the pre-experimental variety. Before and after receiving the Effluerage Massage intervention, participants completed the EPDS questionnaire. The massage lasted around 30 minutes every other day for a total of 14 days. There were a total of 12 samples collected from first-time mothers who had recently given birth in the Kebasen Health Center's service area between the months of January and March 2023. A paired t-test was utilized in the process of analyzing the data. Results: The paired t-test on postpartum mothers who underwent Effleurage massage showed a probability value of ρ-value 0.000 0.05, this indicates that the null hypothesis was rejected or that the study hypothesis was accepted. After receiving effleurage massage, it is possible to draw the conclusion that there is a statistically significant difference in the EPDS scores of first-time mothers who have recently given birth. Conclusion: Effleurage massage effectively reduces EPDS scores in primiparous postpartum mothers.Keywords: Effleurage massage, score, EPDS, primipara